AB0820 Psoriatic Arthritis Mutilans Cohort Attending St. Vincent'S University Hospital: Demographics and Clinical Characteristics. (9th June 2015) - Elmamoun, M.; Haroon, M.; Gallagher, P.; FitzGerald, O.
Abstract : Background: Psoriatic Arthritis (PsA) affects about 30% of individual with psoriasis after an average interval of 10 years (1, 2). The most common classification of PsA by Moll and Wright still remains widely in use (3). The criteria include five clinical subgroups of PsA according to the pattern of joint involvement: oligoarthritis, polyarthritis, distal small joint arthritis, spondylarthritis, and Arthritis Mutilans (AM). AM is a rare type of PsA. In the literature the prevalence of AM has been estimated to range from zero or just 1% (4, 5) up to 8% (6) of the PsA population. Objectives: To determine the demographic and clinical characteristics of psoriatic AM in an Irish cohort attending a rheumatology unit. Methods: Patients with a diagnosis of PsA, fulfilling the CASPAR criteria, who have AM, defined by digital shortening, erosion involving entire articular surfaces on both sides of the joint and/or pencil-in-cup change and/or osteolysis, aged >18 years were recruited. 23 patients were included after clinical and radiological examinations. Results: The female to male ratio was close to 2:1. The mean age was 56.52. The mean age of skin disease onset was 24 years and the mean age of onset of joint disease was 30 years. At inclusion, the mean duration of arthritis was 25.8 years ±9.9 years. The only pattern of arthritis was that of polyarticular disease; with 48% of patients exhibiting concomitant axial disease. Enthesitis was found in 8 patients (35%), while 13 patients (57%) had dactylitis. 8 patients (35%) had sacroiliitis on plain films, 6 of these patients (75%) had asymmetrical sacroiliitis. 21 patients (91%) had nail disease. None of the patients in this cohort had uveitis. At the time of inclusion, 70% of patients were found to have clear or almost clear skin. 16 patients were on biologics (75%). The most frequent joints that showed AM were the MTP joints on the fourth toe on the left foot (n=10), followed by MTP joints on the fourth toe on the right (n=9). Further characteristics are outlined table 1 . Conclusions: The prevalence of AM in our psoriatic arthritis cohort is approximately 8%. The majority of patients present with nail disease, and mild skin disease. The average interval between skin and joint disease is approximately 6 years. AM occurs in the setting of poly articular disease and frequent axial involvement. The axial disease in these patients tends to be asymmetrical sacroiliitis. Many patients require biologics to control their disease. References: Mease PJ, Gladman DD, et al: Prevalence of rheumatologist-diagnosed psoriatic arthritis in patients with psoriasis in European/North American dermatology clinics, J Am Acad Dermatol. 69(5):729-35, 2013 Gladman DD, et al. Psoriatic arthritis (PSA): an analysis of 220 patients. Q J Med 1987;62:127–41 Moll JMH, Wright V. Psoriatic arthritis. Semin Arthritis Rheum. 1973;3:55–78. Tam LS, Leung YY, Li EK. Psoriatic arthritis in Asia. Rheumatology (Oxford) 2009;48:1473–7. Scarpa R. Clinical manifestation and diagnosis of psoriatic arthritis. Rheumatology in Europe 1998;27:130–2. Koo T, Nagy Z, et al. Subsets in psoriatic arthritis by cluster analysis. Clin Rheumatol 2001;20:36–43. Disclosure of Interest: None declared